Effects of C-1-substituted glucose analogue on the activation states of glycogen synthase and glycogen phosphorylase in rat hepatocytes. - Board, M; Bollen, M; Stalmans, W; Kim, Y; Fleet, G; Johnson, L (1995)
A series of glucose-analogue inhibitors of glycogen phosphorylase b (GPb) has been designed, synthesized and investigated in crystallographic binding and kinetic studies. The aim is to produce a compound that may exert more effective control over glycogen metabolism than the parent glucose molecule and which could alleviate hyperglycaemia in Type-II diabetes. N-Acetyl-beta-D-glucopyranosylamine (1-GlcNAc) has a Ki for muscle GPb in crude extracts of 30 microM, 367-fold lower than that of beta-D-glucose [Board, Hadwen and Johnson (1995) Eur. J. Biochem. 228, 753-761]. In the current work, the effects of 1-GlcNAc on the activation states of GP and glycogen synthase (GS) in cell-free preparations and in isolated hepatocytes are reported. In gel-filtered extracts of liver, which lack ATP for kinase activity, 1-GlcNAc produced a rapid and time-dependent inactivation of GP with a subsequent activation of GS. Effects of 1-GlcNAc on both enzymes were stronger than those of glucose, with 0.8 mM 1-GlcNAc being equipotent with 50 mM glucose. At 1 mM, 1-GlcNAc enhanced the dephosphorylation of exogenous GPa by liver extracts (600%) and by muscle extracts (75%). This represents an approximately 500-fold improvement on glucose for the liver activity and 40-fold for the muscle activity. In whole hepatocytes, 1-GlcNAc showed an approximately 5-fold enhancement of glucose effects for GP inactivation but failed to elicit activation of GS. Glucose-induced activation of GS in whole hepatocytes was reversed by subsequent addition of 1-GlcNAc. However, when GS activation was achieved via the adenosine analogue and kinase inhibitor, 5'-iodotubercidin (ITU), subsequent addition of 1-GlcNAc allowed continued activation of GS. Phosphorylation of 1-GlcNAc in rat hepatocytes was established using radiolabelled material. The rate of phosphorylation was 1.60 nmol/min per 10(6) cells at 20 mM 1-GlcNAc but was reduced by the presence of 50 microM ITU (0.775 nmol/min per 10(6) cells). It is suggested that the phosphorylated derivative of 1-GlcNAc formed in hepatocytes is 1-GlcNAc 6-phosphate and that the presence of this species is responsible for the failure of 1-GlcNAc to activate GS. The relative importance of the reduction in concentration of GPa versus increased glucose 6-phosphate levels for activation of GS is discussed.